The Impact of Learning Strategies on English as a Foreign Language Learners’ Reading Comprehension Skills Development - Desta Wendaferew; Abebe Damtew Berlie (Educational Challenges)
Purpose. The aim of this study was to examine the impact of explicit reading strategy teaching English as a foreign language (EFL) on Ethiopian grade eleven learners’ reading comprehension skills, particularly, reading for the gist, detail, vocabulary, inference, and reference skills.